2013
DOI: 10.1111/j.1467-6494.2013.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

The View From the Looking Glass: How Are Narcissistic Individuals Perceived by Others?

Abstract: Previous studies have found that narcissistic individuals are often viewed negatively by those who know them well. The present study sought to extend these previous findings by examining whether normal and pathological aspects of narcissism were associated with perceiver ratings of narcissistic characteristics and aggression. This was accomplished by having each of our undergraduate participants (288 targets) recruit friends or family members to complete ratings of the target who recruited them (1,296 perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 60 publications
0
12
0
1
Order By: Relevance
“…To assess the manner in which individuals with different levels of self‐esteem were viewed by others, we had to establish some minimum number of perceivers for each target in order for them to be included in the final analyses. As a result, we decided to only include targets in the final analyses who recruited three or more perceivers (see Malkin, Zeigler‐Hill, Barry, & Southard, in press, for a similar strategy). Of the 930 participants who completed the initial questionnaires, 357 participants (58 men and 299 women) recruited three or more perceivers to participate in the study by completing questionnaires about their perceptions of the targets who recruited them (38% of the original sample).…”
Section: Methodsmentioning
confidence: 99%
“…To assess the manner in which individuals with different levels of self‐esteem were viewed by others, we had to establish some minimum number of perceivers for each target in order for them to be included in the final analyses. As a result, we decided to only include targets in the final analyses who recruited three or more perceivers (see Malkin, Zeigler‐Hill, Barry, & Southard, in press, for a similar strategy). Of the 930 participants who completed the initial questionnaires, 357 participants (58 men and 299 women) recruited three or more perceivers to participate in the study by completing questionnaires about their perceptions of the targets who recruited them (38% of the original sample).…”
Section: Methodsmentioning
confidence: 99%
“…Normal narcissism (as measured by the Narcissistic Personality Inventory; NPI; Raskin & Terry, 1988, and its derivatives) is characterized more by personality attributes such as vanity, grandiosity, superiority, entitlement, and self‐promotion (Barry & Malkin, 2010). Finally, pathological narcissism involves emotion dysregulation and experiencing negative emotions on a consistent basis (see Malkin, Ziegler‐Hill, Barry, & Southard, 2013) and is composed of two domains: grandiose narcissism and vulnerable narcissism. Grandiose narcissism is characterized by an inflated self‐image, maladaptive attempts to enhance that self‐image, and envy of others’ successes (Malkin et al, 2013; Pincus et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, pathological narcissism involves emotion dysregulation and experiencing negative emotions on a consistent basis (see Malkin, Ziegler‐Hill, Barry, & Southard, 2013) and is composed of two domains: grandiose narcissism and vulnerable narcissism. Grandiose narcissism is characterized by an inflated self‐image, maladaptive attempts to enhance that self‐image, and envy of others’ successes (Malkin et al, 2013; Pincus et al, 2009). Vulnerable narcissism involves a much more fragile presentation and is characterized by feelings of helplessness, insecurity, and hypersensitivity to how one is perceived (Miller et al, 2011; Pincus et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings further indicate that perceived intellectual self‐enhancement is linked to social impressions. Hence, they provide further evidence that informant or peer perceptions of one's level of self‐enhancement are linked to evaluative judgments of that person (Anderson et al, ; Malkin et al, ). These findings, however, were more intricate than the ones pertaining to actual intellectual self‐enhancement.…”
Section: Discussionmentioning
confidence: 95%
“…When the target was described as someone who overestimates his social status, he was rated low in social attractiveness. Malkin, Zeigler‐Hill, Barry, and Southard () found that targets seen by informants as possessing grandiose self‐views were subsequently judged as high in instrumental overt aggression. Taken together, the evidence suggests that perceived self‐enhancement is linked to low social attractiveness and the attribution of aggression as a social influence tactic.…”
Section: Social Impressions Of Actual and Perceived Intellectual Selfmentioning
confidence: 99%